Cathepsins and their inhibitors as tumor markers in head and neck cancer - Strojan, Primož (Radiology and oncology (Ljubljana), 2004)
The invasion and metastasizing of tumor cells is closely connected with the disintegration of basement membranes and extracellular matrix. The carriers ofthese processes are different proteolytic enzymes, among them cysteine and aspartic cathepsins B, H, L and D as well, a group of ubiquitous lysosomal proteases, and endogenous inhibitors of the former, cystatins. The aim of the present review was to collect the current knowledge on the predictive and prognostic value of cathepsins and their inhibitors in squamous cell carcinomaof the head and neck. In this particular tumor type, the UICC/AJCC TNM-classification system and histopathological characteristics of the tumors were found inadequate to reliably predict either the response to therapy or patients' survival. Moreover, to date, no factor within the wide spectrum of biochemical and histological factors has yet been idenrified as reliably predicting the natural course of the disease or its response to therapy. To construct a prognostically meaningful tumor profile, new markers are intensively investigated.
Keywords: Carcinoma, Squamous Cell; Cathepsins; Cistatini; Cystatins; diagnostika; glava; Glava in vrat, novotvorbe; Head And Neck Neoplasms; karcinom; Karcinom ploščatocelični; Katepsini; Limfatična metastaza; Lymphatic Metastasis; onkologija; Prognosis; Prognoza; rak (medicina); tumorski označevalci; vrat; Vrata